PENERAPAN MOTION GRAPHIC PADA IKLAN LAYANAN MASYARAKAT “DUA FAKTA” - Astuti, Aprilina Dwi (Institut Seni Indonesia Padang Panjang, 2024)
Public Service Advertisements (PSAs) are the process of conveying information, which is persuasive and educational in nature. For this reason, the packaging of PSAs needs to be packaged carefully in order to produce work that is easily understood by the audience. One way to package PSAs to produce interesting and easy-to-understand impressions needs to be packaged using motion graphics. The aim of this research is to apply motion graphics to the production of the public service advertisement